Population trends of striped hyena (Hyaena hyaena) in Israel for the past five decades - Ezra Hadad; Jakub Z. Kosicki; Reuven Yosef (Scientific Reports, 2023)
Abstract The striped hyena (Hyaena hyaena) is considered “Near Threatened” globally and “Vulnerable” in the Middle East. In Israel, the species has experienced extreme population fluctuations owing to poisoning campaigns during the British Mandate (1918–1948) which were also further exacerbated by the Israeli authorities in the mid-twentieth century. We collated data from the archives of the Israel Nature and Parks Authority for the past 47 years to elucidate the temporal and geographic trends of this species. During this period we found a 68% increase in population and the estimated density is at present 2.1 individuals/100km2. This is significantly higher than all previous estimates for Israel. It appears that the major factors contributing to their phenomenal increase in number are the increase in prey availability because of the intensification of human development, preying on Bedouin livestock, the extinction of the leopard (Panthera pardus nimr), and the hunting of wild boars (Sus scorfa) and other agricultural pests in some parts of the country. Reasons should also be sought in increasing people's awareness as well as in advanced technological capabilities that have allowed an improved observation and reporting system. Future studies need to understand the effects of the large concentrations of striped hyenas on the spatial distribution and temporal activity of other sympatric wildlife to ensure the continued persistence of the wildlife guilds in the Israeli nature.